Dilemmas Of The English-Melanau Translators In Sarawak Language Technologies Project - Surian Khartini, Jali; Noralifah, Annuar; Nurul Zawiyah, Mohamad; Ting, Su Hie; Salbia, Hassan (Centre for Academic Information Services, UNIMAS, 2014)
The Sarawak Language Technology (SaL T) project aims to preserve languages through the use of language technologies such as machine translation of English and Bahasa Melayu to indigenous languages in Sarawak. and vice versa. As part of the larger project. a study was conducted to examine the difficulties encountered by the Melanau native speakers who were engaged to translate English texts to Melanau to provide the source data for the development of the English-Melanau translation software. A total of 20 Melanau translators were involved in the translation of a corpus of 1098 English sentences approximating 10,534 words (Including repeated words such as aku, kamu, dia). The translators were educated in English and Bahasa Melayu, and they had jobs ranging from government officers, teachers and students. They did not have degrees in translation but were chosen because of their familiarity with Melanau, English and/or Bahasa Melayu. The Interviews with the Melanau translators indicated that the areas of difficuffies include Melanaa being an oral language without a standardised spelling system, the foreignness of certain concepts to the Melanau language and culture as well as their unfamiliarity with particular expressions and concepts in the source language, English. Insights on improvements in the methodology of obtaining English-Melanau translations were also obtained from the study.